2019
DOI: 10.5578/turkjsurg.4340
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of spironolactone against hepatic ischemia/reperfusion injury in rats

Abstract: Objective: In the present study, it was aimed to study the antioxidant effects of spironolactone (SPL) to determine its possible protective effects in hepatic ischemia reperfusion injury. Material and Methods: Hepatic artery, portal vein, and bile duct of Wistar albino rats were clamped for 45 minutes under anesthesia to form an ischemia period. Then reperfusion was allowed and the rats were decapitated 60 minutes later. SPL (20 mg/kg, p.o.) or SF was orally administered for 30 minutes before ischemia. Rats in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The present study demonstrated that there was a significant increase in hepatic immunohistochemical expression of NF‐κB p65 and serum TNF‐α and IL‐6 levels in rats exposed to HIR compared to sham‐operated groups, which is in accordance with Kamel and colleagues, 5,11,33 who reported that ROS produced soon after reperfusion are the key players in inducing activation of NF‐κB. The phosphorylation of NF‐κB triggers the production of TNF‐α and other proinflammatory cytokines, which in turn leads to further liver damage 36 . Moreover Yoon et al 29 mentioned that the inflammatory reactions notably cause tissue damage that results from HIR.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The present study demonstrated that there was a significant increase in hepatic immunohistochemical expression of NF‐κB p65 and serum TNF‐α and IL‐6 levels in rats exposed to HIR compared to sham‐operated groups, which is in accordance with Kamel and colleagues, 5,11,33 who reported that ROS produced soon after reperfusion are the key players in inducing activation of NF‐κB. The phosphorylation of NF‐κB triggers the production of TNF‐α and other proinflammatory cytokines, which in turn leads to further liver damage 36 . Moreover Yoon et al 29 mentioned that the inflammatory reactions notably cause tissue damage that results from HIR.…”
Section: Discussionsupporting
confidence: 87%
“…5,8,[33][34][35] According to Rabie et al, 11 transaminases are reliable markers for estimating the severity of acute liver injury because they are highly expressed in the serum following the damage of liver cells. In addition, Atalay et al 36 pointed out that although there are a number of techniques for evaluating the liver functions in case of IR injury, measuring AST and ALT activities is now considered to be the most popular technique because it is known that the activities of these enzymes increase after hepatic injury. On the other hand, HIR rats pretreated with ang-(1-7) had significantly lower serum levels of AST and ALT than HIR rats.…”
Section: Immunohistochemistry For Anti-p53 Antibodymentioning
confidence: 99%
See 1 more Smart Citation
“…Such pattern persisted until the end of the experiment, which allowed the aldosterone effects to manifest themselves. That is why, no significant increase in liver enzymes and TNF-α was observed in rats injected with aldosterone antagonists 30 minutes prior to the IRP simulation [17]. Therefore, we conclude that an increase in aldosterone after systemic IRP stimulates liver damage, while its antagonists have hepatoprotective properties.…”
Section: Discussionmentioning
confidence: 67%
“…TNF-α directly contributes to liver injury by activating or triggering important infl ammatory factors and increasing neutrophil infi ltration and parenchymal damage. Similarly, IL-1β causes liver cell damage with some effects, such as activating NF-kB, increasing leukocyte aggregation, and upregulating TNF-α production by Kupffer cells (17,25,26). Some studies have reported that Ambroxol reduces the production and release of cytokines (10,11).…”
Section: Discussionmentioning
confidence: 99%